CRISPR/Cas9 knockout of HAS2 in rat chondrosarcoma chondrocytes demonstrates the requirement of hyaluronan for aggrecan retention - Huang, Yi (East Carolina University, 2016)
Hyaluronan (HA) plays an essential role in cartilage where it functions to retain aggrecan. Previous studies suggested that aggrecan is anchored indirectly to the plasma membrane of chondrocytes via its binding to cell-associated HA. However, reagents used to test these observations such as hyaluronidase and HA oligosaccharides are short term and may have side activities that complicate interpretation. Using the CRISPR/Cas9 gene editing approach, a model system was developed by generating HA-deficient chondrocyte cell lines. HA synthase-2 (Has2)-specific single guide RNA was introduced into two different variant lines of rat chondrosarcoma chondrocytes; knockout clones were isolated and characterized. Two other members of the HA synthase gene family were expressed at very low relative copy number, but showed no compensatory response in the Has2 knockouts. Wild type chondrocytes of both variants exhibited large pericellular matrices or coats extending from the plasma membrane. Addition of purified aggrecan monomer expanded the size of these coats as the proteoglycan became retained within the pericellular matrix. Has2 knockout chondrocytes lost all capacity to assemble a particle-excluding pericellular matrix and more importantly, no matrices formed around the knockout cells following the addition of purified aggrecan. When grown as pellet cultures so as to generate a bioengineered neocartilage tissue, the Has2 knockout chondrocytes assumed a tightly-compacted morphology as compared to the wild type cells. When knockout chondrocytes were transduced with Adeno-ZsGreen1-mycHas2, the cell-associated pericellular matrices were restored including the capacity to bind and incorporate additional exogenous aggrecan into the matrix. These results suggest that HA is essential for aggrecan retention and maintaining cell separation during tissue formation. Further, the Has2 KO cell lines provide a useful new tool to study HA and chondrocyte function.
Keywords: Hyaluronan synthase-2; Hyaluronic Acid; Aggrecans; Animals; Cartilage, Articular; Chondrocytes; Chondrosarcoma; Clustered Regularly Interspaced Short Palindromic Repeats; Glucuronosyltransferase; Rats